Growth and development of sugar sorghum (Sorghum saccharatum L. Pers.) plants at different terms of sowing and seeding depth in the Forest-Steppe of Ukraine - Л. А. Герасименко (Plant Varieties Studying and Protection)
The article features the results of research on phenological observations, biometric parameters of growth and development of the plants of sugar sorghum Silosnoe 42 variety during the vegetation at different terms of sowing and seeding depth in the Forest-Steppe of Ukraine. In particular, we show data on ground germination capacity of the seeds, the duration of the interphase periods, tillering, plant height and the diameter of the stem. It was established that the planting of sugar sorghum in mid-May (the third sowing date) to the seeding depth of 4...6 cm enabled better plant development, as well as in these conditions the maximum values of plant growth and development were registered compared to the other test editions. Therefore, were would suggest the third term of sowing and seed depth 4...6 cm for growing the crop in this area.